An Analysis Of The Enlightening Values In The Novel Kite Runner By Khaled Hosseini - S, K. Dedy Sandiarsa; Suhaili, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was aimed to find out the enlightening values of The Kite Runner Novel. The statement of the problem. Was “What were the enlightening values in The Kite Runner Novel. The method on this study was qualitative descriptive. There werefour steps for Techniques of data collection were collective from the novel itself,documentation, reading the novel the kite runner novel was the from the first pages until the last pages. Re-reading and the last is identifying. In analyzing the data, the researcher used three steps, namely data reduction, data display and conclusion and drawing or verification. Those aretwo types of data found, namely values of being and values of giving. The two types of data found the parts of data giving namelytwo loyalties and trustworthy, two loves affection and six kindsof friendly. The data found are values of being with eleven data and values of giving ten data. Found two honesties, five bravely, one peace ability, two confident and potential and one discipline and moderation.